Virome of red imported fire ants by metagenomic analysis in Guangdong, southern China - Li, Qiuxu; Lian, Yingjie; Zhang, Ketong; Chen, Jinchao; Chen, Long; Wu, Jiandong; Zhang, Yangyang; Chen, Minyi; Zhang, Weize; Lu, Mengke; Ma, Jun; Bai, Aiquan (Frontiers in Microbiology, 2024)
The red imported fire ant (RIFA) has made China its habitat for approximately 25 years, but few reports have described the species and amount of virus circulating in it. Researchers are currently exploring viruses associated with RIFAs as potential biological control agents against invasive ants. The present meta-transcriptome analysis revealed the virome of red imported fire ants in Guangdong, southern China, which included 17 viruses, including Solenopsis invicta virus 4-GD (SINV-4) and Guangdong Polycipiviridae ant virus 1 (GPAV1) in the Polycipiviridae family; Solenopsis invicta virus 1-GD (SINV-1), and Guangdong Dicistroviridae ant virus 2-3 (GDAV2-3) in the Dicistroviridae family; Guangdong Iflaviridae ant virus 4-9 (GIAV4-9) in the Iflaviridae family; Guangdong Parvoviridae ant virus 10 (GPAV10) in the Parvoviridae family; and Guangdong ant virus 11-15 (GAV11-15). A total of 15 novel viruses and 2 known viruses were identified in this study. These findings reveal the virome of red imported fire ants in Guangdong Province and present a different result from that of a similar study reported in the United States, providing more choices for potential classical biological control agents against red imported fire ants in China.